High-salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel, preparation method and application thereof

CN117586550BActive Publication Date: 2026-10-09SHANDONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311276688.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-10-05
Filing Date
2023-10-05
Publication Date
2026-10-09
Estimated Expiration
2043-10-05

AI Technical Summary

Technical Problem

[0007]针对现有制备Janus结构气凝胶方法合成过程复杂、能耗高、污染大等诸多问题,本发明提供一种高耐盐P(AM-DMDAAC)/石墨烯基大孔Janus气凝胶及其制备方法与应用

Benefits of technology

[0039] 1. This invention selects a low-cost dimethyl diallyl ammonium chloride acrylamide polymer modification material, abbreviated as P(AM-DMDAAC). It is a linear binary cationic copolymer rich in quaternary ammonium ions, formed by copolymerizing dimethyl diallyl ammonium chloride (DMDAAC) and acrylamide (AM). It can be used as a precursor to bond with two or more graphene sheets through electrostatic interactions, effectively preventing graphene aggregation. At the same time, the hydrophilic edges of the graphene sheets can bond with the P(AM-DMDAAC) branches through hydrogen bonds and van der Waals forces, thereby promoting the self-assembly of the three-dimensional graphene hydrogel. This improves the poor mechanical properties of graphene aerogel to a certain extent, greatly enhancing the mechanical properties of the aerogel and giving it a stronger ability to withstand risks in natural environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117586550B_ABST
    Figure CN117586550B_ABST
Patent Text Reader

Abstract

The application relates to a high-salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel and a preparation method and application thereof, which is prepared by mixing P(AM-DMDAAC) and graphene oxide in a certain proportion under hydrothermal conditions to synthesize the graphene-based macroporous Janus aerogel in one step. The P(AM-DMDAAC) / graphene-based macroporous Janus aerogel shows asymmetric wettability and roughness on the upper and lower surfaces, is beneficial to the photo-thermal conversion of the hydrophobic interface and the sufficient water supply of the hydrophilic interface, and has an evaporation rate of 3.65 kg m ‑2 h ‑1 under the irradiation of one sunlight. Benefited from the excellent water supply performance and the special Janus structure, the obtained aerogel shows strong recyclability and salt resistance in actual seawater evaporation, the surface of the aerogel does not appear any salt crystallization within 10 days, has the advantages of high evaporation efficiency, good stability, strong salt pollution resistance and the like, and has a wide prospect in actual production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel, its preparation method, and its applications, belonging to the fields of chemistry and environmental technology. Background Technology

[0002] With rapid socio-economic development, industrial water consumption has increased dramatically along with the growth of production scale. Simultaneously, wastewater production is also constantly increasing. The pesticide, dye, and pharmaceutical industries generate large amounts of high-salinity wastewater during production. This wastewater has complex pollutant compositions, is difficult to treat, and severely pollutes soil and water bodies, causing serious consequences such as soil salinization, water eutrophication, and even air pollution, thus severely impacting the ecological environment. Compared to developed countries, my country's industrial wastewater reuse rate is relatively low. Therefore, low-cost resource utilization of high-salinity wastewater has become a new challenge in the environmental field. Resource utilization can not only minimize the pollution risks of wastewater to the environment but also reduce the pressure on ecosystems caused by freshwater extraction.

[0003] Currently, advanced desalination technologies such as forward osmosis, reverse osmosis, multi-stage flash evaporation, and membrane distillation have been put into practical production. However, the high construction, operation, and maintenance costs limit the development of freshwater production in remote areas. Solar-driven interfacial evaporation has attracted widespread attention due to its efficient and convenient freshwater production process, and photothermal conversion materials are key to achieving low cost and high efficiency in this technology.

[0004] In the solar-driven interfacial evaporation process, a thin water film covers the interface of the photothermal conversion material. Aerogels can maximize photothermal conversion and utilize the generated heat to produce fresh water, significantly reducing heat loss to the bulk water and surrounding area, thus improving energy utilization efficiency. Simultaneously, to ensure the efficient and stable operation of the solar-driven interfacial evaporation process, the photothermal material must possess excellent water transfer properties and resistance to salt crystallization, while maintaining high photothermal conversion efficiency and its own evaporation performance. This prevents the accumulation of salt crystals during long-term evaporation, which could block water supply channels and reduce vapor pressure; and avoids the precipitation of salt crystals covering the photothermal layer, leading to a significant reduction in captured solar light and inhibiting photothermal conversion. Graphene aerogel, as a novel three-dimensional material, has low density, good thermal insulation, and high porosity, possessing high photothermal conversion efficiency and an excellent evaporation rate that breaks through the evaporation limit. However, due to the interaction of van der Waals forces and π-π bonds, graphene sheets exhibit stacking, which significantly reduces the mechanical properties of graphene aerogels. Therefore, functionalization is urgently needed to enhance its mechanical properties.

[0005] The study of Janus-structured aerogels is currently a hot research topic. Common modification methods include selective fluorination, silane modification, and carbonization. However, these methods generally involve first preparing a hydrophilic aerogel and then modifying it. The preparation processes of these methods are relatively complex, thus limiting large-scale practical applications. Therefore, there is an urgent need to construct a Janus-structured aerogel with a simple preparation process, readily available raw materials, and excellent photothermal conversion and wetting properties. Currently, there are no reports of using a one-step method to prepare three-dimensional Janus-structured aerogels for photothermal evaporation.

[0006] Chinese patent document CN113603935A discloses a composite aerogel with Janus properties, using cellulose nanofiber powder and Ti3C2T x Using MXene dispersion as raw material, silane-modified cellulose nanofibers / Ti3C2T were obtained by freeze-drying. x MXene aerogel was used as the upper layer material; cellulose nanofiber dispersion was immersed in liquid nitrogen and frozen to obtain cellulose nanofiber aerogel as the lower layer material. The upper and lower layers were chemically cross-linked at the interface to form a whole. The aerogel prepared by this method achieved a water evaporation rate of 2.331 kg m³ under standard sunlight. -2 h -1 After 10 consecutive days of standard sunlight exposure (6 hours per day), its evaporation rates in 3.5 wt%, 7 wt%, and 10.5 wt% NaCl aqueous solutions reached 2.13, 2.03, and 1.80 kg m³, respectively. -2 h -1 The composite aerogel with Janus properties is prepared by first preparing an upper layer and a lower layer, and then connecting them into a whole through chemical cross-linking at the interface between the upper and lower layers. The preparation process is complicated, costly, and can easily cause environmental pollution. Summary of the Invention

[0007] To address the numerous problems associated with existing methods for preparing Janus-structured aerogels, such as complex synthesis processes, high energy consumption, and significant pollution, this invention provides a highly salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel, its preparation method, and its applications. Invention Overview:

[0009] This invention uses P(AM-DMDAAC) and graphene oxide as raw materials, mixes them in a certain proportion, and synthesizes graphene-based macroporous Janus aerogel in one step under hydrothermal conditions. Since P(AM-DMDAAC) is positively charged, it can cleverly combine with negatively charged graphene sheets through electrostatic interaction, effectively suppressing graphene stacking caused by van der Waals forces and π-π bond interactions. After the reaction is completed, a hydrogel is formed. The hydrogel is placed vertically in a container with a flat inner surface, exposing its upper surface and contacting the bottom of the container with its lower surface. It is then freeze-dried directly without pre-freezing, finally obtaining a highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel with a hydrophobic upper surface and a hydrophilic lower surface. Invention Details:

[0011] This invention is achieved through the following technical solution:

[0012] A highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel is described. The composite aerogel is prepared by constructing a three-dimensional network structure using graphene oxide as raw material and P(AM-DMDAAC) as a modifier through a one-step hydrothermal-cryogenic casting method. One side of the Janus aerogel is a rough hydrophobic surface, while the opposite side is a smooth hydrophilic surface, and the interior has a porous structure.

[0013] According to a preferred embodiment of the present invention, the water contact angle of the hydrophobic surface is 130-140°, and the water contact angle of the hydrophilic surface is 0°; the material exhibits an evaporation rate of 3.606 kg m³ in deionized water under solar irradiation at one intensity. -2 h -1 After 10 cycles of 5-hour evaporation in actual seawater or 10wt% NaCl solution, no salt formation was observed on its surface; the ion removal rate reached over 99%.

[0014] The second objective of this invention is to provide a method for preparing the above-mentioned high salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel.

[0015] The preparation method of the above-mentioned high salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel includes the following steps:

[0016] (1) P(AM-DMDAAC) was placed in deionized water and stirred overnight to obtain a homogeneous P(AM-DMDAAC) solution;

[0017] (2) Graphene oxide was placed in deionized water and ultrasonically dispersed evenly to obtain a uniform and stable graphene oxide dispersion.

[0018] (3) Adjust the pH of the graphene oxide dispersion, and then mix and stir it with the P(AM-DMDAAC) solution to obtain a mixed dispersion;

[0019] (4) The mixture of step (3) was hydrothermally treated and cooled to obtain a hydrogel. The hydrogel was soaked and washed with deionized water. The washed hydrogel was placed in a container with a smooth and flat inner surface, so that its upper surface was exposed and its lower surface was in contact with the bottom of the container with a smooth and flat inner surface. It was freeze-dried to obtain a high salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel.

[0020] According to a preferred embodiment of the present invention, in step (1), the concentration of the P(AM-DMDAAC) solution is 3-10 mg / mL, and the stirring time is 12-24 h.

[0021] More preferably, the concentration of the P(AM-DMDAAC) solution is 4-8 mg / mL, and the stirring time is 15-20 h.

[0022] According to a preferred embodiment of the present invention, in step (2), the concentration of the graphene oxide dispersion is 4-10 mg / mL, the ultrasonic dispersion power is 200-600 W, and the ultrasonic time is 30-300 s.

[0023] Further preferably, the concentration of the graphene oxide dispersion is 4-6 mg / mL, and the ultrasonic time is 60-180 s.

[0024] According to a preferred embodiment of the present invention, in step (3), the pH of the post-oxidized graphene dispersion is adjusted to 2-11.

[0025] More preferably, in step (3), the pH of the graphene oxide dispersion is adjusted to 9-11.

[0026] According to a preferred embodiment of the present invention, in step (3), the volume ratio of the graphene oxide dispersion to the P(AM-DMDAAC) solution is (1-2):(1-2).

[0027] More preferably, in step (3), the volume ratio of the graphene oxide dispersion to the P(AM-DMDAAC) solution is 1:1.

[0028] According to a preferred embodiment of the present invention, in step (4), the hydrothermal reaction temperature is 150-250℃ and the reaction time is 5-15h.

[0029] According to a preferred embodiment of the present invention, in step (4), the soaking and washing time is 24-72h, and the deionized water is replaced every 6h; the freeze-drying conditions are: temperature -40℃~-50℃, vacuum degree 0-10Pa, and drying time 24-40h.

[0030] According to a preferred embodiment of the present invention, in step (4), the material of the container is not limited, such as glass or plastic, as long as the inner bottom surface is smooth and flat.

[0031] A third objective of this invention is to provide an application of a highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel.

[0032] Application of a highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel for photothermal evaporation, seawater desalination, or high-salt wastewater desalination treatment.

[0033] According to a preferred embodiment of the present invention, the specific method of photothermal evaporation is as follows: a solar evaporation device is constructed, which consists of a foam ring, a cylindrical sponge, and P(AM-DMDAAC) / graphene-based macroporous Janus aerogel. The foam ring is fixed to one end of the cylindrical sponge and placed on the water surface. The sponge contacts the water body to form a T-shaped water supply device. The aerogel is placed on the top of the T-shaped water supply device, and the bottom surface contacts the wetted sponge. The aerogel is continuously transported to the hydrophobic upper surface by means of the wetted sponge for efficient photothermal evaporation.

[0034] According to a preferred embodiment of the present invention, the specific method for desalination is as follows: placing a high salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel in water bodies with different salt concentrations, evaporating it for 5 hours under the condition of one sun's light intensity, and collecting the purified water obtained from evaporation.

[0035] This invention prepares a structurally stable three-dimensional aerogel by combining P(AM-DMDAAC) with negatively charged graphene sheets through a one-step hydrothermal reaction, effectively suppressing the occurrence of stacking phenomena; effectively suppressing the aggregation of graphene caused by van der Waals forces and π-π bond interactions; while improving mechanical properties, by controlling the reaction conditions, the prepared aerogel also has a Janus structure, that is, it has the characteristics of hydrophobic upper surface and hydrophilic lower surface, so that its upper and lower surfaces exhibit asymmetric wettability and roughness, which is conducive to photothermal conversion at the hydrophobic interface and sufficient water supply at the hydrophilic interface. It can ensure sufficient water supply while having a certain degree of hydrophobicity, thereby effectively condensing the heat in the photothermal layer, improving evaporation efficiency, and enhancing salt resistance.

[0036] This invention uses P(AM-DMDAAC) to functionalize graphene to prepare an aerogel with a Janus structure, which can be used for the evaporation and desalination of high-salt water.

[0037] The Janus aerogel of this invention has a macroporous structure, serving as a continuous reverse water transport channel. This prevents salt crystals from concentrating and depositing on a hydrophobic surface. Salt crystals redissolve in water with the aid of capillary forces. Furthermore, salt solubility is positively correlated with temperature; under 1.0°C sunlight irradiation, the temperature of the hydrophobic surface of the aerogel can reach 41.6°C, significantly higher than the temperature of water. Therefore, high temperatures exacerbate salt dissolution. In addition, the convection and diffusion effects caused by salinity differences also provide a driving force for the redissolution of salt crystals. This series of properties not only endows the aerogel with good salt resistance but also with excellent self-cleaning ability, thus exhibiting high salt tolerance.

[0038] The beneficial effects of this invention are as follows:

[0039] 1. This invention selects a low-cost dimethyl diallyl ammonium chloride acrylamide polymer modification material, abbreviated as P(AM-DMDAAC). It is a linear binary cationic copolymer rich in quaternary ammonium ions, formed by copolymerizing dimethyl diallyl ammonium chloride (DMDAAC) and acrylamide (AM). It can be used as a precursor to bond with two or more graphene sheets through electrostatic interactions, effectively preventing graphene aggregation. At the same time, the hydrophilic edges of the graphene sheets can bond with the P(AM-DMDAAC) branches through hydrogen bonds and van der Waals forces, thereby promoting the self-assembly of the three-dimensional graphene hydrogel. This improves the poor mechanical properties of graphene aerogel to a certain extent, greatly enhancing the mechanical properties of the aerogel and giving it a stronger ability to withstand risks in natural environments.

[0040] 2. This invention utilizes a one-step hydrothermal-cryogenic casting method to obtain Janus-structured photothermal evaporation materials with hydrophobic upper surfaces and hydrophilic lower surfaces, exhibiting different wettability, without requiring further material modification. Compared to other modification methods, the one-step hydrothermal-cryogenic casting method is simple, does not produce any toxic or harmful substances during synthesis, and does not cause secondary pollution to the ecological environment.

[0041] 3. The high salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel of this invention possesses extremely high photothermal conversion efficiency, capable of absorbing sunlight and efficiently converting it into heat energy. Furthermore, due to its extremely low thermal conductivity (0.0291 W / m²), it exhibits excellent thermal conductivity. -1 K -1 It has excellent thermal insulation properties, reducing heat loss to the surrounding environment.

[0042] 4. The highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel of this invention can absorb water through its hydrophilic lower surface and transport it to the upper surface. Due to the low affinity of the upper surface for water, it cannot be wetted, thus forming a thin water film beneath the surface. Thermal energy is efficiently used to heat the water film, avoiding energy dissipation caused by directly heating the water, thereby greatly improving energy utilization efficiency. The evaporation rate can reach 3.65 kg m³. -2 h -1 It is nine times the natural evaporation rate of pure water under the same environmental conditions. Meanwhile, the photothermal conversion efficiency can reach 98.9%.

[0043] 5. In applications such as seawater desalination and simulating high-salinity wastewater, the P(AM-DMDAAC) / graphene-based macroporous Janus aerogel of this invention exhibits extremely high salt resistance. This is because the Janus structure helps prevent salt crystallization. Due to the strong hydrophobicity of the upper surface, seawater is blocked below the surface layer, thus preventing salt from easily precipitating to the surface. This ensures unimpeded steam escape, and the upper surface can continuously capture sunlight for photothermal conversion. Even when high salinity leads to salt crystallization on the upper surface, the excellent hydrophilicity of the lower surface allows water to be continuously transported upwards. The salt crystals can redissolve and diffuse back into the water due to the salt concentration gradient and capillary action. Therefore, the evaporation rate of the aerogel does not decrease drastically and remains at a high level.

[0044] 6. This invention prepares Janus-structured aerogels using a one-step hydrothermal-freeze casting method. Due to the different pressures on the upper and lower surfaces of the hydrogel during the hydrothermal process, the resulting hydrogel exhibits different roughness and morphology on its upper and lower surfaces. During the 48-hour freeze-drying process, no pre-freezing is required; the aerogel is placed vertically with its lower surface close to the container, while the upper surface does not need to contact the container. The aerogels obtained through this method exhibit significant differences in hydrophilicity / hydrophobicity and structure between their upper and lower surfaces.

[0045] The features and advantages of the present invention will be described in detail through embodiments and in conjunction with the accompanying drawings. Attached Figure Description

[0046] Figure 1 A comparison of the contact angles of the upper and lower surfaces of P(AM-DMDAAC) / graphene-based macroporous Janus aerogels prepared under different P(AM-DMDAAC) concentrations, graphene dispersion concentrations, and pH conditions.

[0047] Figure 2The roughness morphology (CLSM) images of the upper and lower surfaces of the Janus aerogel prepared in Example 1 and the unmodified graphene aerogel prepared in Comparative Example 1 are shown below; a is the upper surface of the Janus aerogel prepared in Example 1, b is the lower surface of the Janus aerogel prepared in Example 1, c is the upper surface of the unmodified graphene aerogel prepared in Comparative Example 1, and d is the lower surface of the unmodified graphene aerogel prepared in Comparative Example 1.

[0048] Figure 3 The images show the microstructure (SEM) of the upper and lower surfaces of the Janus aerogel prepared in Example 1 of this invention; ac represents the upper surface of the Janus aerogel, and df represents the lower surface of the Janus aerogel.

[0049] Figure 4 The graph shows the change in the upper surface temperature of the aerogels prepared in Example 1, Comparative Examples 1 and 2 over time.

[0050] Figure 5 This is a schematic diagram of the compression strain of the aerogel prepared in Example 1 after fifteen compression-release cycle tests.

[0051] Figure 6 The absorption spectra of the upper and lower surfaces of Example 1 and Comparative Examples 1 and 2 in the 200-2500 nm wavelength range are shown.

[0052] Figure 7 A comparison of the evaporation rates of P(AM-DMDAAC) / graphene-based macroporous Janus aerogels prepared under different P(AM-DMDAAC) concentrations, graphene dispersion concentrations, and pH conditions.

[0053] Figure 8a The curves showing the changes in water evaporation rate in actual seawater and 10wt% NaCl solution are shown in Example 1.

[0054] Figure 8b The curves showing the change in water evaporation rate of simulated high-salt wastewater (20wt% NaCl solution) in Example 1 are shown.

[0055] Figure 8 The diagram shows the salt deposition on the upper surface during the evaporation of actual seawater and 10wt% NaCl solution in Example 1. c represents actual seawater, and d represents 10wt% NaCl solution.

[0056] Figure 9 This is a schematic diagram showing the changes in the concentration of various ions in the water before and after desalination of actual seawater and simulated high-salt wastewater (20wt% NaCl solution) in Example 1; a is a schematic diagram showing the changes in ion concentration before and after actual seawater desalination, and b is a schematic diagram showing the changes in ion concentration before and after desalination of simulated high-salt wastewater (20wt% NaCl solution).

[0057] Figure 10 The graph shows the trend of evaporation rate as the outdoor evaporation experiment of Example 1 (10h) changes with real-time outdoor environmental conditions (including ambient temperature and sunlight intensity). Detailed Implementation Plan

[0058] The method for preparing highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel according to the present invention will be described in detail below with reference to specific embodiments and accompanying drawings.

[0059] All raw materials and reagents used in the examples were commercially available products.

[0060] P(AM-DMDAAC) in the example is available from Shandong Binzhou Jiayuan Environmental Protection Co., Ltd.

[0061] Example 1

[0062] A method for preparing a highly salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel, comprising the following steps:

[0063] (1) Weigh 120mg of graphene oxide into a beaker, add 20ml of deionized water, sonicate at room temperature for 2min to obtain a uniform graphene dispersion, and adjust its pH to 9.

[0064] (2) Weigh 80 mg of P(AM-DMDAAC) into a beaker, add 20 ml of deionized water, stir overnight to obtain a homogeneous P(AM-DMDAAC) solution;

[0065] (3) The graphene dispersion and P(AM-DMDAAC) solution were mixed and stirred evenly at a volume ratio of 1::1, and then transferred to a polytetrafluoroethylene inner liner. The mixture was placed in a reaction vessel and subjected to hydrothermal reaction at 200°C for 8 hours to obtain P(AM-DMDAAC) / graphene composite hydrogel.

[0066] (4) Place the P(AM-DMDAAC) / graphene composite hydrogel in deionized water and soak for 24 hours for washing;

[0067] (5) The washed hydrogel was placed in a container with a smooth inner surface, exposing its upper surface and contacting the bottom of the container with its lower surface. It was then placed in a freeze dryer and freeze-dried for 48 hours to obtain a high salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel.

[0068] Example 2

[0069] The preparation method of the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel described in Example 1 differs in that:

[0070] In step (1), the amount of graphene oxide used is 80 mg, and the rest of the operation and dosage are exactly the same as in Example 1.

[0071] Example 3

[0072] The preparation method of the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel described in Example 1 differs in that:

[0073] In step (1), the amount of graphene oxide used is 160 mg, and the rest of the operation and dosage are exactly the same as in Example 1.

[0074] Example 4

[0075] The preparation method of the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel described in Example 1 differs in that:

[0076] In step (1), the amount of graphene oxide used is 200 mg, and the rest of the operation and dosage are exactly the same as in Example 1.

[0077] Example 5

[0078] The preparation method of the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel described in Example 1 differs in that:

[0079] In step (1), the dosage of P(AM-DMDAAC) is 0 mg, and the rest of the operation and dosage are exactly the same as in Example 1.

[0080] Example 6

[0081] The preparation method of the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel described in Example 1 differs in that:

[0082] In step (1), the dosage of P(AM-DMDAAC) is 60 mg, and the rest of the operation and dosage are exactly the same as in Example 1.

[0083] Example 7

[0084] The preparation method of the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel described in Example 1 differs in that:

[0085] In step (1), the dosage of P(AM-DMDAAC) is 120 mg, and the rest of the operation and dosage are exactly the same as in Example 1.

[0086] Example 8

[0087] The preparation method of the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel described in Example 1 differs in that:

[0088] In step (1), the dosage of P(AM-DMDAAC) is 180 mg, and the rest of the operation and dosage are exactly the same as in Example 1.

[0089] Example 9

[0090] The preparation method of the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel described in Example 1 differs in that:

[0091] In step (1), the pH of the graphene dispersion is 2, and the rest of the operation and dosage are exactly the same as in Example 1.

[0092] Example 10

[0093] The preparation method of the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel described in Example 1 differs in that:

[0094] In step (1), the pH of the graphene dispersion is 5, and the rest of the operation and dosage are exactly the same as in Example 1.

[0095] Example 11

[0096] The preparation method of the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel described in Example 1 differs in that:

[0097] In step (1), the pH of the graphene dispersion is 7, and the rest of the operation and dosage are exactly the same as in Example 1.

[0098] Example 12

[0099] The preparation method of the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel described in Example 1 differs in that:

[0100] In step (1), the pH of the graphene dispersion is 11, and the rest of the operation and dosage are exactly the same as in Example 1.

[0101] Comparative Example 1

[0102] The preparation method of the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janu aerogel described in Example 1 differs in that:

[0103] The amount of P(AM-DMDAAC) used was 0 mg, the pH of the graphene dispersion was 2, and the rest of the operation and dosage were exactly the same as in Example 1.

[0104] Comparative Example 2

[0105] The preparation method of the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel described in Example 1 differs in that:

[0106] The amount of P(AM-DMDAAC) used was 0 mg, the pH of the graphene dispersion was 9, and the rest of the operation and dosage were exactly the same as in Example 1.

[0107] Performance testing

[0108] 1. Measurement of contact angles of upper and lower surfaces

[0109] The contact angles of the upper and lower surfaces of the Janus aerogels prepared in Examples 1-12 are as follows: Figure 1 As shown, Figure 1 a corresponds to the change in the contact angle of the upper and lower surfaces of aerogels prepared with different amounts of P(AM-DMDAAC). The results show that as the amount of P(AM-DMDAAC) doping increases, the contact angle of the upper surface of the composite aerogel first increases and then decreases, while the contact angle of the lower surface remains at 0°.

[0110] Figure 1 b corresponds to the change in the contact angle of the upper and lower surfaces of aerogels prepared with different graphene dosages. The results show that as the amount of graphene increases, the contact angle of the upper surface of the composite aerogel first increases and then decreases, while the contact angle of the lower surface remains at 0°.

[0111] Figure 1 c corresponds to the change in the contact angles of the upper and lower surfaces of aerogels prepared using graphene dispersions with different pH values. The results show that as the pH of the graphene dispersion increases, the contact angle of the upper surface of the composite aerogel first decreases and then increases, while the contact angle of the lower surface remains at 0°.

[0112] 2. Confocal microscope image

[0113] Confocal microscopy images of the aerogels prepared in Example 1 and Comparative Example 1 are shown below. Figure 2 ,pass Figure 2 It can be seen that, compared with Comparative Example 1, the upper surface of Example 1 is rougher and the lower surface is smoother, indicating that the addition of P(AM-DMDAAC) promotes the formation of the Janus structure.

[0114] 3. Electron micrograph

[0115] The electron micrograph of the composite aerogel prepared in Example 1 is shown below. Figure 3 ,pass Figure 3 It can be seen that, compared to a smooth and flat lower surface ( Figure 3The upper surface is rougher, consisting of scaly, layered grooves formed by crisscrossing mesh fibers and a three-dimensional macroporous structure. Figure 3 ac).

[0116] 4. Mechanical property testing

[0117] The aerogel prepared in Example 1 was subjected to compression cycle tests at 70% compressive strain as follows: Figure 4 The results show that, compared with Comparative Example 1, the composite aerogel prepared in Example 1, after fifteen cycles of testing, maintained constant material strain while gradually decreasing compressive stress, but the aerogel did not completely break down, demonstrating its ability to withstand risks under harsh external conditions.

[0118] 5. Photothermal performance test

[0119] The surface temperature variation trend of the aerogels prepared in Example 1, Comparative Examples 1 and 2 under one solar radiation intensity is shown in the figure below. Figure 5 The results showed that, compared with Comparative Examples 1 and 2, the surface temperature of the composite aerogel prepared in Example 1 could rise to a higher level in a shorter time, indicating that the addition of P(AM-DMDAAC) improved the aerogel's ability to capture sunlight.

[0120] The absorption spectra of the upper and lower surfaces of the aerogels prepared in Example 1, Comparative Examples 1 and 2 in the 200-2500 nm wavelength range are as follows: Figure 6 The results showed that, compared with Comparative Examples 1 and 2, the composite aerogel prepared in Example 1 had stronger absorption of sunlight on both its upper and lower surfaces, which may be attributed to the introduction of P(AM-DMDAAC). Meanwhile, the absorption rate of the upper surface was higher than that of the lower surface, which is due to the abundant three-dimensional fibrous macroporous structure on the upper surface of the aerogel, giving it better light-harvesting ability.

[0121] 6. Evaporation performance test

[0122] The evaporation rates of aerogels prepared with different dosages of GO and P(AM-DMDAAC) and different pH values ​​of graphene dispersions in deionized water under a single solar radiation intensity were compared. Figure 7 The results showed that the composite aerogel prepared when the dosage of graphene and P(AM-DMDAAC) was 120 mg and 80 mg, respectively, and the pH value of the graphene dispersion was 9, had a higher evaporation rate. This was due to the high hydrophobicity of its upper surface, indicating that the addition of P(AM-DMDAAC) improved the photothermal evaporation capacity of the aerogel.

[0123] 7. Salt resistance test

[0124] The evaporation rate of the highly salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel in actual seawater in Example 1 is as follows: Figure 8a As shown, the results indicate that during 10 cycles of solar-driven evaporation experiments (each cycle lasting 5 hours, followed by the PGA being left untouched on the apparatus for 24 hours after each cycle, and then placed in the air for 24 hours before the next cycle), no salt crystallization occurred on the aerogel surface. Figure 8 c). Meanwhile, its evaporation rate did not decrease significantly, remaining at a high level, reaching a maximum of 3.74 kg m³. -2 h -1 .

[0125] The evaporation rate of the highly salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel in 10 wt% NaCl solution in Example 1 is as follows: Figure 8a As shown, the results indicate that during the 10-cycle solar-driven evaporation experiment, no significant salt precipitation occurred on the aerogel surface in the first 5 days. However, starting from day 3, significant salt deposition began to appear on the foam rings, gradually becoming more severe with increasing evaporation days. On day 6, after 5 hours of evaporation under 1.0 irradiance, salt crystals began to appear on the surface, but the evaporation rate did not decrease. After being left overnight, the hydrophobic upper surface became as clean as new before the start of the next cycle. The salt crystals redissolved into the bulk water with the aid of capillary forces. Figure 8 d). Meanwhile, its evaporation rate decreased slightly in the first few days, but remained at 3.21 kg m³ after 10 days. -2 h -1 Around 100°C, no significant decrease occurred.

[0126] The evaporation rate of the highly salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel in 20 wt% NaCl solution in Example 1 is as follows: Figure 8b As shown, the results indicate that after evaporation for 5 hours under 1.0 ppm sunlight, no salt crystals formed on the surface, and the evaporation rate remained at 3.40 kg / m³. -2 h -1 Left and right, with no obvious fluctuations.

[0127] The following describes the application of highly salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel prepared under optimal synthesis conditions in water desalination.

[0128] Application Experiment Example 1

[0129] Example 1: Purification of seawater and high-salt water bodies using highly salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel. Figure 9 As shown, the results indicate that the main cations in seawater (Na) +K + Ca 2+ and Mg 2+ It can be removed quickly, with a removal efficiency of over 99.1%. Figure 9 a). Even in the treatment of high-salinity wastewater, the removal efficiency of Na+ concentration reached 99.99% ( Figure 9 b). The collected purified water ion concentration was lower than the World Health Organization (WHO) standard.

[0130] Application Experiment Example 2

[0131] The evaporation performance of the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel in Example 1 under actual outdoor sunlight is as follows: Figure 10 As shown, the results indicate that the natural solar radiation intensity from 11:00 to 13:00 is close to 1.0 kW m². -2 The evaporation rate of the aerogel reached 3.51 kg m³. -2 h -1 After a 10-hour outdoor evaporation experiment, no salt crystals appeared on the surface of the aerogel.

Claims

1. A highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel, wherein the highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel is synthesized in one step by mixing P(AM-DMDAAC) and graphene oxide as raw materials and reacting them under hydrothermal conditions. Since P(AM-DMDAAC) is positively charged, it cleverly combines with the negatively charged graphene sheets through electrostatic interaction, effectively suppressing the graphene stacking caused by van der Waals forces and π-π bond interactions. After the reaction is completed, a hydrogel is formed. The hydrogel is placed vertically in a container with a flat inner surface, exposing its upper surface and contacting the bottom of the container with its lower surface. It is then freeze-dried directly without pre-freezing, finally obtaining a highly salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel with a hydrophobic upper surface and a hydrophilic lower surface.

2. The high salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel according to claim 1, characterized in that, The hydrophobic surface has a water contact angle of 130-140°, while the hydrophilic surface has a water contact angle of 0°. Under solar irradiation at a given intensity, the material exhibits an evaporation rate of 3.606 kg·m³ in deionized water. -2 ·h -1 After 10 cycles of 5h evaporation in actual seawater and 10wt% NaCl solution, no salt formation was observed on its surface; the ion removal rate reached over 99%.

3. The preparation method of the high salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel according to claim 1, comprising the following steps: (1) P(AM-DMDAAC) was placed in deionized water and stirred overnight to obtain a homogeneous P(AM-DMDAAC) solution; (2) Graphene oxide was placed in deionized water and ultrasonically dispersed evenly to obtain a uniform and stable graphene oxide dispersion. (3) Adjust the pH of the graphene oxide dispersion and mix it with the P(AM-DMDAAC) solution to obtain a mixed dispersion; (4) The mixture of step (3) was hydrothermally treated and cooled to obtain a hydrogel. The hydrogel was soaked and washed with deionized water. The washed hydrogel was placed in a container with a smooth and flat inner surface, so that its upper surface was exposed and its lower surface was in contact with the bottom of the container with a smooth and flat inner surface. It was freeze-dried to obtain a high salt-resistant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel.

4. The preparation method according to claim 3, characterized in that, In step (1), the concentration of P(AM-DMDAAC) solution is 3-10 mg / mL, and the stirring time is 12-24 h.

5. The preparation method according to claim 3, characterized in that, In step (1), the concentration of P(AM-DMDAAC) solution is 4-8 mg / mL, and the stirring time is 15-20 h.

6. The preparation method according to claim 3, characterized in that, In step (2), the concentration of the graphene oxide dispersion is 4-10 mg / mL, the ultrasonic dispersion power is 200-600 W, and the ultrasonic time is 30-300 s.

7. The preparation method according to claim 3, characterized in that, In step (3), the pH of the graphene oxide dispersion was adjusted to 2-11, and the volume ratio of the graphene oxide dispersion to the P(AM-DMDAAC) solution was (1-2):(1-2).

8. The preparation method according to claim 3, characterized in that, In step (4), the hydrothermal reaction temperature is 150-250℃, the reaction time is 5-15h, the soaking and washing time is 24-72h, and the deionized water is replaced every 6h; the freeze-drying conditions are: temperature -40℃~-50℃, vacuum degree is 0-10Pa, and drying time is 24-40h.

9. The application of the high salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel according to claim 1, for photothermal evaporation, seawater desalination, or high-salt wastewater desalination treatment.

10. The application according to claim 9, characterized in that, The specific method of photothermal evaporation is as follows: Construct a solar evaporation device, which consists of a foam ring, a cylindrical sponge, and P(AM-DMDAAC) / graphene-based macroporous Janus aerogel. The foam ring is fixed to one end of the cylindrical sponge and placed on the water surface. The sponge contacts the water body to form a T-shaped water supply device. The aerogel is placed on the top of the T-shaped water supply device, with its bottom surface in contact with the wetted sponge. The aerogel is continuously transported to the hydrophobic upper surface by the wetted sponge to achieve efficient photothermal evaporation. The specific method for desalination is as follows: place the high salt-tolerant P(AM-DMDAAC) / graphene-based macroporous Janus aerogel in water bodies with different salt concentrations, evaporate it for 5 hours under the condition of one sun's light intensity, and collect the purified water obtained from evaporation.

Citation Information

Patent Citations

  • Composite aerogel with Janus characteristic as well as preparation method and application thereof

    CN113603935A

  • Graphene-based three-dimensional macro body as well as preparation method and application thereof

    CN105271211A

  • Graphene-based aerogel with asymmetric wettability and preparation method and application thereof

    CN109081331A